2021
DOI: 10.3389/fdata.2021.662011
|View full text |Cite
|
Sign up to set email alerts
|

Using 3D CityGML for the Modeling of the Food Waste and Wastewater Generation—A Case Study for the City of Montréal

Abstract: The paper explains a workflow to simulate the food energy water (FEW) nexus for an urban district combining various data sources like 3D city models, particularly the City Geography Markup Language (CityGML) data model from the Open Geospatial Consortium, Open StreetMap and Census data. A long term vision is to extend the CityGML data model by developing a FEW Application Domain Extension (FEW ADE) to support future FEW simulation workflows such as the one explained in this paper. Together with the mentioned s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In 2021, Braun et al [ 43 ] utilized 3D CityGML to model food waste and wastewater patterns in the city of Montreal. Employing the 3D CityGML framework, they conducted simulations to discern trends in waste generation and dispersion throughout the urban landscape.…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, Braun et al [ 43 ] utilized 3D CityGML to model food waste and wastewater patterns in the city of Montreal. Employing the 3D CityGML framework, they conducted simulations to discern trends in waste generation and dispersion throughout the urban landscape.…”
Section: Methodsmentioning
confidence: 99%
“…Inspired by the concept of Energy ADE, a recent JPI Urban Europe project IN-SOURCE ("INtegrated analysis and modelling for the management of sustainable urban food water energy ReSOURCEs") developed a Food-Water-Energy (FWE) ADE data model to study the nexus of food, water and energy systems (Padsala et al, 2021). Within IN-SOURCE, different renewable potential workflows such as photovoltaic potential (roofs, fac ¸ade and open field) (Bao et al, 2023), bio-energy (Bao et al, 2020), AgriPV (Bao et al, 2022) and energy recovery from food and water waste (Braun et al, 2021) were developed in SimStadt and successfully tested using FWE ADE enriched CityGML building and landuse model of the entire district of Ludwigsburg in Germany. In a different JPI Urban Europe project, SUNEX ("Sustainable Urban food water energy NEXus"), the energy demand model MAED-City (Model for evaluation of energy demand of City) was adapted and used to project future long-term final energy demand of the cities Vienna, Berlin, Bristol and Doha.…”
Section: State Of Artmentioning
confidence: 99%
“…Additionally, FWE ADE was deployed as a central data exchange platform to exchange data between SimStadt and a FWE land use simulator UD InfraSim to simulate future biomass potential of a land-use scenario influenced by climate, population and urban development changes in Vienna (Padsala et al, 2021a). (Braun et al, 2021) identified new objects and attributes which can be a part of FWE ADE supporting circular economy workflows, such as energy recovery from food waste and water waste with a potential to extend it for storing carbon emissions stemming from household consumption of food type (plant-based or animalbased) and that from the transportation of food waste to the loc-ation of landfills.…”
Section: Use Of Urban Digital Twins In Sustainable Urban Developmentmentioning
confidence: 99%